2015
DOI: 10.1210/me.2015-1021
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: Androgen Receptor Activity Is Regulated Through the Mobilization of Cell Surface Receptor Networks

Abstract: The aberrant expression of androgen receptor (AR)-dependent transcriptional programs is a defining pathology of the development and progression of prostate cancers. Transcriptional cofactors that bind AR are critical determinants of prostate tumorigenesis. To gain a deeper understanding of the proteins linked to AR-dependent gene transcription, we performed a DNA-affinity chromatography-based proteomic screen designed to identify proteins involved in AR-mediated gene transcription in prostate tumor cells. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 124 publications
0
5
0
Order By: Relevance
“…Studies have showed that there is a positive correlation between TNF-α and TGF-β and TP53 mutations ( 106 , 109 ). Aberrant expression of androgen receptor (AR) -dependent transcriptional programs is a decisive pathology in the development of prostate cancer, and studies have shown that TNF-α and TGF-β can be involved in mediating AR-dependent gene transcription ( 107 ). Radiation can induce persistent genomic instability of bone marrow cells in mice, which is associated with high expression of TNF-α with TGF-β ( 110 ).TGF-β can up-regulate the activity of the pseudoxanthoma elasticum genesis gene ABCC6 promoter in HepG2 cells, while TNF-α has the opposite effect ( 108 ).…”
Section: Interaction Between Tnf-α and Tgf-βmentioning
confidence: 99%
“…Studies have showed that there is a positive correlation between TNF-α and TGF-β and TP53 mutations ( 106 , 109 ). Aberrant expression of androgen receptor (AR) -dependent transcriptional programs is a decisive pathology in the development of prostate cancer, and studies have shown that TNF-α and TGF-β can be involved in mediating AR-dependent gene transcription ( 107 ). Radiation can induce persistent genomic instability of bone marrow cells in mice, which is associated with high expression of TNF-α with TGF-β ( 110 ).TGF-β can up-regulate the activity of the pseudoxanthoma elasticum genesis gene ABCC6 promoter in HepG2 cells, while TNF-α has the opposite effect ( 108 ).…”
Section: Interaction Between Tnf-α and Tgf-βmentioning
confidence: 99%
“…AR-positive mesenchymal cells are required for normal fetal gubernacular development and testicular descent, and transgenic deletion of Ar in these cells interferes with normal muscle development (Kaftanovskaya et al, 2012). Interestingly, SYNE2, ANKRD28 and PARG were recently identified as novel AR-interacting proteins in prostate cancer cells (Hsiao et al, 2015). A role for cryptorchidism risk genes participating at multiple levels in hormonal pathways required for gubernacular development and testicular descent is biologically plausible, but defining a role for these LE/orl cryptorchidism susceptibility candidates in muscle development, hormone production and/or AR signaling will require further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In combination, these MS-based characterization efforts on AR transcriptional complexes have considerably expanded the spectrum of its coregulators and cofactors. Alternatives are possible, for instance (MS) analyses of complexes bound to ARE-containing regions [93,94]. A limitation of the approaches above is the potential for aspecific interactions or false positives to be detected by MS, emphasizing the need for stringent analysis and experimental validation of MS data [95].…”
Section: Biotin-based Proximity Ligation Assaymentioning
confidence: 99%